2011
DOI: 10.1140/epja/i2011-11108-2
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive measurement of the pp → nnπ+π+ reaction at 1.1 GeV

Abstract: First exclusive data for the pp → nnπ + π + reaction have been obtained at CELSIUS with the WASA detector setup at a beam energy of Tp = 1.1 GeV. Total and differential cross sections disagree with theoretical calculations, which predict the ∆∆ excitation to be the dominant process at this beam energy. Instead the data require the excitation of a higher-lying ∆ state, most likely the ∆(1600), to be the leading process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…As a result of these kinematically complete and exclusive two-pion production measurements at CELSIUS and subsequently at COSY it was shown that all pp induced, i.e. all isovector channels, behave as expected from conventional t-channel excitation of Roper, ∆∆ (mutual excitation of the colliding nucleons into their first excited state ∆(1232)) and ∆(1600) resonances [8,9,10,11,12,13,14,15,16,17].…”
Section: Exclusive and Kinematically Complete Experiments -Observatiomentioning
confidence: 88%
“…As a result of these kinematically complete and exclusive two-pion production measurements at CELSIUS and subsequently at COSY it was shown that all pp induced, i.e. all isovector channels, behave as expected from conventional t-channel excitation of Roper, ∆∆ (mutual excitation of the colliding nucleons into their first excited state ∆(1232)) and ∆(1600) resonances [8,9,10,11,12,13,14,15,16,17].…”
Section: Exclusive and Kinematically Complete Experiments -Observatiomentioning
confidence: 88%
“…The analysis of the pp → nnπ + π + reaction gives about 15 µb [15] for this cross section at T p = 1.25 GeV, which results in…”
Section: Two-pion Productionmentioning
confidence: 95%
“…In recent years the two-pion production in pp and pn collisions has been measured by exclusive and kinematically complete experiments over the energy region from threshold up to T lab = 1.4 GeV [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Two-pion Productionmentioning
confidence: 99%
“…Starting first with the WASA/PROMICE detector setup, followed by the completed WASA detector at CELSIUS and finally at COSY all ppinduced, i.e. isovector two-pion production channels from threshold up to √ s = 2.5 GeV have been studied [323,324,325,326,327,328,329,330,331] complemented by a corresponding program with polarized beam at COSY-TOF [314,332]. The results for the total cross sections are shown in Fig.…”
Section: No Dibaryon Signal In Pp-induced Two-pion Productionmentioning
confidence: 99%
“…As a result it was found [350] that there is, indeed, a highly visible low-mass enhancement but no high-mass enhancement as seen in previous σ 0 π + π pn → pp Figure 9: Energy dependence of the pp-induced total cross sections for two-pion production and their isospin decomposition. Open symbols denote results from bubble-chamber measurements [317,318,319,320,321,322], solid symbols represent measurements from WASA/PROMICE (triangles) [323,324,325], CELSIUS/WASA (circles) [326,327,328,329,330] and COSY-TOF (squares) [314]. At the top the reaction channels pp → ppπ 0 π 0 (left) and pp → nnπ + π + (right) are shown together with their isospin decomposition.…”
Section: Following a Trace: The Abc Effectmentioning
confidence: 99%